The Semantic Meaning of the Russian Riddle - Mukhitdinovna, Babakhodjaeva Nigora (European Journal of Life Safety and Stability (2660-9630), 2023)
In this article dicusses the semantic space of Russian folk riddles about nature, which is a real linguistic problem. He researched the nominations that define "Nature" in Russian riddles, determining the nature itself and its expressions, the time of day, the flora and animals. "Nature" is represented by a great number of lexemes in the article's selected material, characterizing it as a live, living being. This allows the author to argue that anthropomorphism and subjectivity are the fundamental elements of Russian riddle semantic space.